Approach to modulate the sensing range of molecular transducers - Jain, Bhanprakash; Dharmapurikar, Satej S. (Sensors and Actuators B-Chemical, 2015)
Transduction occurs upon binding of an analyte with a transducer. Specific binding involves the design and synthesis of receptors that is non trivial. Indeed, the task of designing a receptor for the smallest anion fluoride is very challenging. Herein, we take advantage of the basicity of fluoride ions that has affinity toward acidic proton. A commercially available 6-bromoisatin can sense fluoride ion in the concentration range of 0.5-3.9 ppm. Although the sensor is reaction based, the response is rapid. To further increase the linear range, dibromoisoindigo was synthesized. The linear range of this transducer was found to be between 0.5 ppm and 10.4 ppm. The transducer can be regenerated by adding proton source such as trifluoroacetic acid. Thus, transducers with variable sensing range have been designed and synthesized using acid base interaction. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Acidic proton; Basicity; Fluoride ion; Reversible sensor; Transducers